IMPLEMENTASI SISTEM INFORMASI ONLINE LAYANAN ADMINISTRASI (SiOLA) KEMENTERIAN DALAM NEGERI - Muhidin, Enjang; Saksono, R. N. Afsdy; Giyanto, Bambang (Jurnal Academia Praja, 2024)
The Implementation of a policy is important. It is even mentioned to be more important than planning in a management system. SiOLA is one of the policies issued by the Ministry of Home Affairs of the Republic of Indonesia (Kemendagri) to tackle various problems in communicating with the public regarding administrative services. This research aims to determine the causing factors the lack of optimal implementation of the Ministry of Home Affairs' Online Administration Service Information System (SiOLA). The used method is a qualitative research method with a case study approach. Data collection was carried out through observation, interviews and document review. The research results indicate that several factors cause the implementation of SiOLA as a form of implementing an Electronic Based Government System (SPBE) or e-government is not optimal. The theory using is Van Meter Van Horn, which analyzes factors that are not yet optimal. Firstly, the Resource (Human) Factor, in the form of there still being authorized officials, who handle consultation themes in the relevant Work Units are not yet fully implementing the SOP (Not updating service progress, so it cannot be tracked. Secondly, Attitude and Behavioral Characteristic Factors, in the form of the results of the 2023, Community Satisfaction Survey Report, which have been exposed, there are still opinions from service user respondents, who assess that the implementation of SiOLA still has weaknesses in its management. Thirdly, Social, Economic and Political Environment (Economy) Factors, in the form of an increase in the number of visits, which is due to the belief that direct services are more convincing; the attractiveness of the City of Jakarta and the existence of official travel compensation.